Whole-brain structure–function coupling abnormalities in mild cognitive impairment: a study combining amplitude of low-frequency fluctuations and voxel-based morphometry - Zhao, Rong; Wang, Pan; Liu, Lin; Zhang, Fanyu; Hu, Peng; Wen, Jiaping; Li, Hongyi; Biswal, Bharat B. (Frontiers in Neuroscience, 2023)
Alzheimer's disease (AD), one of the most leading nervous system diseases, is accompanied by symptoms including loss of memory, thinking, and language ability. Both mild cognitive impairment (MCI) and very MCI (VMCI) are the transitional pathological stage between normal ageing and AD. While the changes to whole-brain structural and functional information have been extensively investigated in AD, the impaired structure-function coupling remains unknown. Current study employed the OASIS-3 dataset including 53 MCI, 90 VMCI and 100 age-, gender-and education-matched normal controls (NC). Several structural and functional parameters including amplitude of low frequency fluctuations (ALFF), voxel-based morphometry (VBM) and ALFF/VBM ratio were used to estimate the whole-brain neuroimaging changes among MCI, VMCI and NC. As the disease symptoms became more severe, these regions distributing in the frontal-inf-orb, putamen, and paracentral-lobule within white matter (WM) exhibited progressively increasing ALFF (ALFFNC < ALFFVMCI < ALFFMCI), which was similar as the tendency for the cerebellum and putamen within gray matter (GM). Additionally, as the symptoms got worse in AD, cuneus/frontal lobe within WM and parahippocampal gyrus/hippocampus within GM showed progressively decreasing structure-function coupling. As the typical focal areas in AD, the parahippocampal gyrus and hippocampus exhibited the significantly positive correlations with severity of cognitive impairment, suggesting the important applications of ALFF/VBM ratio in brain disorders. On the other hand, these findings from WM functional signals provided a novel opinion for understanding the pathophysiological mechanisms involving cognitive decline in AD.